Tetrandrine inhibits aldosterone synthesis by covalently targeting CYP11A1 to attenuate hypertension - Chu, Simeng; Yang, Wei; Lu, Yujie; Li, Junjie; Peng, Jiamin; Liu, Wenjuan; Jiang, Min; Bai, Gang (Frontiers in Pharmacology, 2024)
Background: Tetrandrine (Tet) is the main pharmacological component of Stephania tetrandra S. Moore, a well-documented traditional Chinese medicine known for its diuretic and antihypertensive properties. Unraveling the specific targets and mechanisms of Tet involved in inducing diuresis and mitigating hypertension can provide valuable insights into its therapeutic effects.Objective: This study aimed to explore the diuretic and antihypertensive targets and mechanisms of Tet using chemical biology coupled with activity analyses in vivo and in vitro.The diuretic effects of Tet were evaluated using a water-loaded mouse model.The direct target proteins for the diuretic and antihypertensive effects of Tet were determined using chemical biology. Furthermore, the molecular mechanism of Tet binding to target proteins was analyzed using a multidisciplinary approach based on the structure and function of the proteins. Finally, the effects of the Tet-targeted protein on downstream signaling pathways and blood pressure were evaluated in hypertensive model rats.Results: Tet exhibited significant antihypertensive and potassium-preserving diuretic effects. The mechanism underlying these effects involves the modulation of the enzyme activity by covalent binding of Tet to Cys423 of CYP11A1. This interaction alters the stability of heme within CYP11A1, subsequently impeding electron transfer and inhibiting aldosterone biosynthesis.This study not only revealed the mechanism of the diuretic and antihypertensive effects of Tet but also discovered a novel covalent inhibitor of CYP11A1. These findings contribute significantly to our understanding of the therapeutic potential of Tet and provide a foundation for future research in the development of targeted treatments for hypertension.